THE EFFECT OF BIFIDOGENIC FACTORS ON THE PROCESS OF CULTIVATION OF PROBIOTIC MICROFLORA IN WHEY - N. M. Panova; O. V. Merkulova; A. D. Lodygin; A. G. Khramtsov (Современная наука и инновации)
The relevance of obtaining functional feed additives enriched with components of animal or plant origin is justified. The effect of a protein-carbohydrate Supplement and protein hydrolysates obtained from skimmed milk and soy milk on the cultivation of Lb. bifidum in subsurface whey was studied. A new generation of feed additives technology has been developed.